Gender: A Learning Process - Paudel, Udaya Raj (NCC Journal, 2025)
Everywhere Man is in the cage, consciously and unconsciously knitted by himself/herself. Gender, for instance, is such a process that imprisons every individual by differentiating between two opposed set of characteristics, social positions and personality traits, masculine and feminine. Indeed, it is almost impossible to remember the first instance when and how an individual knows her/him as a girl or a boy. It is so ubiquitous and unnoticeable that every individual since the cradle to the grave becomes a voracious learner by carrying the burden of gender division. Undoubtedly, gender determines and confines who we are, the roles we play, the way we look, and the thinking pattern of most of us in collaboration with society. For every society is a scandalmonger of gender on the basis of its inherited cultural imagination. And it is perpetually retained through the generations to come. The analysis reveals that it is necessary to uproot and reconstruct the earlier biased mechanism of society that divided humans in two different segments. This research adopts an interpretive critical literary analysis methodology based on the qualitative framework to explore the multi-layered meaning of gender. It contributes to the organizations working in gender issues, policy makers, teaching-learning and for the awareness in the society that gender is systematic learning and construction of the society that requires the course correction.